Handling HTTP Flood Attacks in High-Load Applications Using Akka Actors Model - Tokpayev, Kairat; Bedelbayev, Agyn; Iskendirova, Anar (Ingénierie des systèmes d'Information, 2023)
The subject of this scientific research is the study of the principles of using asynchronous programming methods to process flood attacks and implement effective methods to handle HTTP Flood attacks on servers. The relevance of this research lies in the need to develop a practical example of using the Akka framework implementation for building microservices based on the Scala language. A practical combination of system analysis and observation of successive stages of the formation of the Akka actor to handle an HTTP Flood attack forms the basis of the methodological approach in this research. This provides ample opportunities to handle DDoS attacks in high-load applications through the use of the Akka Actors model, which aligns with the provisions of the Digital Kazakhstan state program. The practical significance of the results obtained in this research lies in the prospect of their implementation in creating microservice systems with strict API rules and a distributed system strategy, capable of handling millions of active users and ignoring potential fraud, including DDoS attacks.